THE ROLE OF THE GOVERNMENT IN INCREASING SALT PRODUCTION IN GAMPONG CEBREK PIDIE DISTRICT ACCORDING TO ISLAMIC LAW - Armaya Halidasari; Arifin Abdullah (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2020)
Production is a tiered work that requires human earnestness, great sacrifice, and centralised power in a certain environment to realise material and spiritual usability. The purpose of this study is to see what obstacles salt farmers face and how the government's role in overcoming these obstacles, as well as how the Islamic economic perspective on the role of government in salt production activities. The role played by the government must be in line with the rules of sharia. The method used in this research is a qualitative method. The results of the study found that the obstacles faced by salt farmers in Cebrek village must be addressed immediately by the relevant agencies for the sake of smooth production and produce the best quality salt. The government involved in this salt production business is the Department of Marine Affairs and Fisheries. Based on the research results, so far the marine and fisheries service has not fully carried out the obligations that must be carried out to increase salt production in Gampong Cebrek. In the perspective of Islamic economics, the government, which has the power to regulate the people including in economic activities, must be able to hold firmly to the foundation of the Qur'an and Sunnah in carrying out its authority to be fair in accordance with the rules and norms that apply in the frame of Sharia.